Estimation of paper conductivity from short duration polarisation–depolarisation current for diagnosis of power transformer. Issue 8 (1st October 2019) - Mishra, Deepak; Haque, Nasirul; Baral, Arijit; Chakravorti, Sivaji
Abstract : The value of paper conductivity provides quantitative evaluation of transformer insulation health. However, proper identification of paper conductivity requires complete profile of polarisation–depolarisation current (PDC). PDC measurement being a time‐consuming offline process generally takes several hours to complete. Furthermore, magnitude of PDC becomes very low at larger value of time, which makes it sensitive to changes in environmental conditions and field noise. Hence, accuracy of paper conductivity identification can be ensured by conducting multiple measurements. This in‐turn prolongs shutdown time of equipment and become less advantageous to utilities. Here, a method is proposed which is capable of estimating paper conductivity using PDC data recorded for only 800 s. The proposed technique is tested on data collected from several real‐life in‐service transformers. In order to illustrate the accuracy of the proposed technique, paper conductivities (calculated from short duration PDC) were compared with those computed using PDC measured for 10, 000 s.